Administration of 5% Tranexamic Acid Cream Reduce the Amount of Melanin as Effective as 4% Hydroquinone Cream in Female Guinea Pigs (Cavia porcellus) Exposed to Ultraviolet-B Light - Nina Marini; Wimpie Pangkahila; AAGP. Wiraguna (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2021)
Introduction: Exposure to ultraviolet B light will increase the amount of melanin which is a common sign of skin aging, one of which is hyperpigmentation which causes psychological impacts, causing social disturbances. Currently, no effective treatment has been found, where hydroquinone as the gold standard provides dangerous side effects, so a more effective and safe material is needed for long-term use. The aim of this study was to prove that tranexamic acid cream was as effective as hydroquinone in reducing the amount of melanin in female guinea pigs (Cavia porcellus) exposed to UVB rays. Methods: This study used a post test only control group design with 36 adult female guinea pigs exposed to UVB rays for 6 weeks at 60mJ/cm2 three times a week. After 2 weeks the guinea pigs were randomly divided into 2 groups with 18 guinea pigs in each group. Group A was given 4% hydroquinone cream and group B was given tranexamic acid cream 5%. Exposure to UVB rays was continued as long as the guinea pig was given the cream treatment. After 42 days the guinea pigs were biopsied to determine the amount of epidermal melanin. Results: The results showed that the mean amount of melanin in the hydroquinone group was 7.40 ± 3.61 and in the tranexamic acid group was 7.27 ± 4.06 (p=0.925; p>0.05). There was no significant difference between the hydroquinone cream group and the tranexamic sour cream group. Conclusion: This study concluded that administration of 5% tranexamic acid cream reduced the amount of melanin as effective as 4% hydroquinone cream in female guinea pigs exposed to UVB light.